Prospective Evaluation of Clinico-Pathological Predictors of Postoperative Atrial Fibrillation: An Ancillary Study From the OPERA Trial. (August 2020) - Corradi, Domenico; Saffitz, Jeffrey E.; Novelli, Deborah; Asimaki, Angeliki; Simon, Caterina; Oldoni, Emanuela; Masson, Serge; Meessen, Jennifer M.T.A.; Monaco, Rodolfo; Manuguerra, Roberta; Latini, Roberto; Libby, Peter; et al.
Abstract : Background: Postoperative atrial fibrillation (POAF) occurs in 30% to 50% of patients undergoing cardiac surgery and is associated with increased morbidity and mortality. Prospective identification of structural/molecular changes in atrial myocardium that correlate with myocardial injury and precede and predict risk of POAF may identify new molecular pathways and targets for prevention of this common morbid complication. Methods: Right atrial appendage samples were prospectively collected during cardiac surgery from 239 patients enrolled in the OPERA trial (Omega-3 Fatty Acids for Prevention of Post-Operative Atrial Fibrillation), fixed in 10% buffered formalin, and embedded in paraffin for histology. We assessed general tissue morphology, cardiomyocyte diameters, myocytolysis (perinuclear myofibril loss), accumulation of perinuclear glycogen, interstitial fibrosis, and myocardial gap junction distribution. We also assayed NT-proBNP (N-terminal pro-B-type natriuretic peptide), hs-cTnT, CRP (C-reactive protein), and circulating oxidative stress biomarkers (F2-isoprostanes, F3-isoprostanes, isofurans) in plasma collected before, during, and 48 hours after surgery. POAF was defined as occurrence of postcardiac surgery atrial fibrillation or flutter of at least 30 seconds duration confirmed by rhythm strip or 12-lead ECG. The follow-up period for all arrhythmias was from surgery until hospital discharge or postoperative day 10. Results: Thirty-five percent of patients experienced POAF. Compared with the non-POAF group, they were slightly older and more likely to have chronic obstructive pulmonary disease or heart failure. They also had a higher European System for Cardiac Operative Risk Evaluation and more often underwent valve surgery. No differences in left atrial size were observed between patients with POAF and patients without POAF. The extent of atrial interstitial fibrosis, cardiomyocyte myocytolysis, cardiomyocyte diameter, glycogen score or Cx43 distribution at the time of surgery was not significantly associated with incidence of POAF. None of these histopathologic abnormalities were correlated with levels of NT-proBNP, hs-cTnT, CRP, or oxidative stress biomarkers. Conclusions: In sinus rhythm patients undergoing cardiac surgery, histopathologic changes in the right atrial appendage do not predict POAF. They also do not correlate with biomarkers of cardiac function, inflammation, and oxidative stress. Abstract : Supplemental Digital Content is available in the text.